Nitrificação e remoção de matéria orgânica carbonácea e sólidos de efluente doméstico em wetland construído de fluxo vertical - Decezaro, Samara Terezinha (2016)
The vertical flow constructed wetlands (VFCW) are attractive systems in the context of on site wastewater treatment, enabling removal of organics and solids and nitrification. However, the satisfactory performance of these reactors depends, in addition to factors such as organic rates and applied hydraulic rates, of hydrodynamic characteristics. Therefore, performance studies and influence hydrodynamic characteristics of VFCW in wastewater treatment are important. The aim of this study was to evaluate the performance of a domestic wastewater treatment system in full scale with a septic tank followed by a VFCW planted with Heliconia psittacorum in nitrification and removal of organics and solids. The septic tank (V = 3.39 m3) was used in primary treatment, and the VFCW (24.5 m2 of surface area) was used in secondary treatment of domestic wastewater. Two operational phases had been evaluated: Phase I Hydraulic load (HL) applied in VFCW was 52.38 mm/d, fragmenting in 4 pulses per day (375 L each pulse); Phase II HL was 54.54 mm/d, with 8 pulses per day (187.5 L each pulse). Besides the variation of influent flow also occurred variation in inflow concentrations, which was higher in phase I. Hydrodynamic tests were performed during the plant development and in different operating conditions using as tracer rhodamine WT. In addition, physical-chemical and biological analyses of wastewater treatment were carried out by means of grab samples. The result of 5 months of operation showed: (i) The operating conditions made possible the micro-organisms adaptation of system (septic tank + VFCW) in domestic wastewater treatment; (ii) With respect to hydrodynamic characteristics of VFCW, it was identified trend of the flow to complete mixing. The average hydraulic retention time (ṫ) was 20 min before planting macrophytes (at the beginning of operation), 17 min after 93 days of plantation and 22 min after 120 days of plantation. When comparing different volumes of pulses, it was found that the application of lower volume pulses (fragmenting daily HL in 8 pulses) provided greater ṫ (26 min); (iii) With respect to performance of the system, the septic tank showed average removal efficiencies of 29%, 46% and 31% for COD, BOD and SS, respectively in phase I and 44%, 45% and 65% for COD , BOD and SS, respectively, during phase II; The VFCW, during phase I, subject to loading of 30.58 g COD/m2.d, 14.54 g BOD/m2.d, 13.11 g SS/m2.d and 3.93 g NH4+-N/m2.d showed an average removal efficiency of 40%, 40%, 32% and 44% for COD, BOD, SS and NH4+-N respectively. In the phase II, the fragmenting of HL in 8 pulses improved the VFCW performance, subjected to loads of 16.87 g COD/m2.d, 8.18 g BOD/m2.d, 4.21 g SS/m2.d and 2.75 g NH4+-N/m2.d, the VFCW had average removal efficiencies of 55%, 61%, 38% and 51% for COD, BOD, SS and NH4+-N, respectively, and, at the end of phase II averaged 58% NH4+-N influent was converted to NO3--N in VFCW.